2016
DOI: 10.1039/c5ra24154e
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic hybrid CH3NH3PbI3 perovskite materials as channels in thin-film field-effect transistors

Abstract: We proposed a new kind of TFT using organic–inorganic hybrid perovskite CH3NH3PbI3 material as the semiconducting channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…In addition to low‐temperature operation, there have been other solutions to mitigate the gate‐screening influence, such as improving the structural quality of the films, optimizing TFT configuration, electrode contact, and operation mode, and modifying MHP stoichiometry and components. Wu et al developed a N 2 ‐flow methylammonium iodide (MAI)‐vapor‐assisted solution process for fully covered and smooth MAPbI 3 channel layer preparation and achieved the record high μ e of 396.2 cm 2 V −1 s −1 . Sirringhaus's group showed that through the optimization of the film microstructure and source–drain contact modifications, it is possible to significantly minimize the instability and hysteresis in TFT characteristics, and they demonstrated a μ e of 0.5 cm 2 V −1 s −1 at RT in TG‐BC MAPbI 3 TFTs with Cytop as the dielectric and polyethylenimine ethoxylated (PEIE) as the interlayer modifying gold electrodes' work function (Figure b,c) .…”
Section: Solution‐processed Metal Halide Perovskite Transistorsmentioning
confidence: 99%
“…In addition to low‐temperature operation, there have been other solutions to mitigate the gate‐screening influence, such as improving the structural quality of the films, optimizing TFT configuration, electrode contact, and operation mode, and modifying MHP stoichiometry and components. Wu et al developed a N 2 ‐flow methylammonium iodide (MAI)‐vapor‐assisted solution process for fully covered and smooth MAPbI 3 channel layer preparation and achieved the record high μ e of 396.2 cm 2 V −1 s −1 . Sirringhaus's group showed that through the optimization of the film microstructure and source–drain contact modifications, it is possible to significantly minimize the instability and hysteresis in TFT characteristics, and they demonstrated a μ e of 0.5 cm 2 V −1 s −1 at RT in TG‐BC MAPbI 3 TFTs with Cytop as the dielectric and polyethylenimine ethoxylated (PEIE) as the interlayer modifying gold electrodes' work function (Figure b,c) .…”
Section: Solution‐processed Metal Halide Perovskite Transistorsmentioning
confidence: 99%
“…While in some studies, e.g. [24,25], high mobility higher than 1 cm 2 Vs −1 has been reported, in some other studies the mobility was found to be weak, when the device was tested at room temperature [26,28], no field-induced transport was observed [11], or the source-drain current was low and the output characteristics were independent of the gate voltage [24]. Table 1 summarizes the electronic characteristics of some perovskite FETs obtained from recent works.…”
Section: Perovskite Fetmentioning
confidence: 99%
“…A high performance perovskite FET should have a fully-covered perovskite channel with low density of grain boundaries (large grains) and effective contacts between the grains, to minimize trap sites and to enhance the charge carrier mobility and lifetime [11,24]. The aforementioned characteristics of a perovskite film is directly affected by the deposition method [25]. Application of spin coating commonly results in a deweted film with poor coverage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As our previous work described [22], SEM and XRD measurements of PbI 2 layers fabricated by spin coating with different solution concentrations were taken.…”
Section: The Characteristics Of Pbi2 Layer Prepared By Different Procmentioning
confidence: 99%